Composition and abundance of stomach contents of the Tropical Silverside, Atherinomorus duodecimals in Southern Guimaras - Solatorio, Patricia Marie Sorilla (2015.)
Diet of fishes are important in assessing interrelationships of marine organism, and yet less is known in this field. This study forms part of a larger study to determine the diet composition of Atherinomorus duodecimalis in Nabinbin bay, Nueva Valencia, Guimaras. Prey items recorded from the guts of the fish were analyzed using COMM cluster analysis. Results show that chime comprised a huge percentage of their gut. Subjecting the non-chyme components to a cluster analysis revealed two major groups: (1) group a composed of size classes 7.0-7.9 and 8.0-8.9 cm, which fed primarily on fish bones, and (2) group b composed of size classes 3.0-6.9, which fed primarily on harpacticoids. In general, Atherinomorus duodecimalis is considered a generalist, based on its wide range of prey items. Furthermore, larger species may possibly be piscivores, however, more evidence is needed to support this hypothesis.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Tropical Silverside, Altherinomorus duodecimals; Southern Guimaras